2000
DOI: 10.1038/sj.bjp.0703714
|View full text |Cite
|
Sign up to set email alerts
|

Rapid activation of basolateral potassium transport in human colon by oestradiol

Abstract: 1 We investigated the eect of oestradiol on basolateral potassium channels in human colonic epithelium. 2 Ion transport was quanti®ed using short circuit current (I sc ) measurements of samples mounted in Ussing chambers. Serosal K transport was studied using nystatin permeabilization of the apical membrane. Intracellular pH changes were quanti®ed using spectro¯ouresence techniques. 3 Experiments were performed with either 10 nM or 1 mM Ca 2+ in the apical bathing solution. With 10 nM Ca 2+ in the apical bathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…Previous data from our laboratory suggest that the rapid onset of the 17-estradiol antisecretory effect is incompatible with a genomic signaling pathway associated with estrogenic action [8][9][10][11][12][13]. In this study, the effects of 17-estradiol on enterotoxin-induced Cl (Fig.…”
Section: Signaling Pathways Involved In the Antisecretory Response Tomentioning
confidence: 51%
See 1 more Smart Citation
“…Previous data from our laboratory suggest that the rapid onset of the 17-estradiol antisecretory effect is incompatible with a genomic signaling pathway associated with estrogenic action [8][9][10][11][12][13]. In this study, the effects of 17-estradiol on enterotoxin-induced Cl (Fig.…”
Section: Signaling Pathways Involved In the Antisecretory Response Tomentioning
confidence: 51%
“…Previous studies have shown that physiological concentrations of 17-estradiol rapidly increase intracellular Ca 2+ concentration [8,9], stimulate protein kinase C (PKC) and cAMP-dependent protein kinase (PKA) activity [10], and modulate several K + conductances in mammalian colonic epithelia [11]. We have also reported that 17-estradiol rapidly inhibits basal and forskolin-stimulated Cl -secretion in rat distal colonic epithelium through inhibition of basolateral KCNQ1 channels [12,13].…”
Section: Introductionmentioning
confidence: 89%
“…To test whether capsaicin affects chloride secretion in mouse colon, proximal and distal colon were mounted in Ussing chambers and the short-circuit current (I sc ) was monitored. In the colon, the I sc elicited by an increase of intracellular cAMP is mainly due to chloride secretion (38). Forskolin (FSK) was used here to activate adenylate cyclase and increase intracellular cAMP content.…”
Section: Capsaicin Blocks Forskolin-dependent Short-circuit Current Imentioning
confidence: 99%
“…Because excessive activation of chloride secretion underlies diarrheal disorders, substances that inhibit this process are of interest for targeted pharmacotherapy. Inhibition of chloride secretion can be accomplished at different levels such as blockade of apical chloride channels (43), blockade of basolateral potassium channels (38,39) and internalization of NKCC1 (11,58). Various natural compounds produced by luminal bacteria such as short-chain fatty acids and ammonium ions can inhibit chloride secretion (47,66).…”
mentioning
confidence: 99%
“…This change in intracellular pH has a significant impact on basolateral K + conductances producing activation of K + ATP channels and inhibition of a calciumdependent potassium channel (K + Ca ) [72,15]. Previous studies have demonstrated that K ATP channels are involved in electrogenic Na + absorption in distal colon [72,74,75]. These results suggest that aldosterone's non-genomic action would lead to a rapid increase in Na + absorption.…”
Section: Regulation Of Ion Transportmentioning
confidence: 81%